Kill creatures - Power, Rory (New York : Delacorte Press, 2025)
One year after Nan's three best friends disappear, no one is more surprised than her when one of them returns--because she is the one who killed them.
Ages 14+
Grades 10-12.
Keywords: Murder -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Young adult fiction; Detective and mystery fiction; Thrillers (Fiction)